2005
DOI: 10.2139/ssrn.877335
|View full text |Cite
|
Sign up to set email alerts
|

Price Convergence Among Indian Cities: A Cointegration Approach

Abstract: Price dynamics in Indian cities were examined using cointegration analysis. We identified and calculated a common trend for prices in 25 major cities in India. Impulse response functions were obtained to calculate the rates of convergence to the prices and we found that the half-life of any shock is very small for Indian cities. Although a close to three-month half-life seems too fast, there is some indication in the literature that half-life can be much smaller than the conventional rates of 3 to 5 years. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
12
1
1
Order By: Relevance
“…It is well known that in the case of a simple AR(1) process the half‐life of a shock can be estimated using the formula ln(2)/0ptprefixln(2)prefixln(trueδ̂)lntrueδ̂, where trueδ̂ denotes the estimated value of the autoregressive coefficient . However, for more complicated processes, such as a higher order AR process or an ARMA process, the previous formula is no longer valid; thus, impulse response functions should be preferred (see, e.g., Goldberg and Verboven, , Morshed, Ahn, & Lee, , and Seong, Morshed, & Ahn, ). Taking this aspect into consideration, we employ the generalized impulse response functions (GIRF) developed by Pesaran and Shin (), which offer the advantage of being invariant to the way shocks in the underlying VAR model are orthogonalized.…”
Section: Empirical Analysismentioning
confidence: 99%
“…It is well known that in the case of a simple AR(1) process the half‐life of a shock can be estimated using the formula ln(2)/0ptprefixln(2)prefixln(trueδ̂)lntrueδ̂, where trueδ̂ denotes the estimated value of the autoregressive coefficient . However, for more complicated processes, such as a higher order AR process or an ARMA process, the previous formula is no longer valid; thus, impulse response functions should be preferred (see, e.g., Goldberg and Verboven, , Morshed, Ahn, & Lee, , and Seong, Morshed, & Ahn, ). Taking this aspect into consideration, we employ the generalized impulse response functions (GIRF) developed by Pesaran and Shin (), which offer the advantage of being invariant to the way shocks in the underlying VAR model are orthogonalized.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Indeed, for 9 out of 14 non-processed food products half-life estimates lie below 3 months, whereas for 16 out of 24 processed food products half-life estimates range between 6 to 12 months. 4 These rates of convergence could be compared with those estimated for Indian cities by Morshed, Ahn, and Lee (2006), who found that the half-life of any shock is close to 3 months, also using monthly data. In the case of Mexico, Sonora (2005) using monthly dissagregated data found half-life convergence rates ranging between one to two years approximately.…”
Section: Speed Of Adjustment and Half-lifementioning
confidence: 94%
“…Frankel and Rose (1996); Doroodian, Jung, and Boyd (1999); Goldberg and Verboven (2005)), but also with reference to price indices across cities within a country, that is, a context characterised by the absence of trade barriers and exchange rate volatility (e.g. Parsley and Wei (1996); Cecchetti, Mark, and Sonora (2002); Esaka (2003); Sonora (2005); Morshed, Ahn, and Lee (2006)). Early empirical literature on the validity of the law of one price …nds little support in favour of the hypothesis, in the sense that large and persistent deviations from the law of one price are found even in those cases where one would least expect them to occur, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…But the slow convergence as found by Cecchetti, et al (2002) in the case of American cities is further puzzling since it is usually believed that trade barriers with in a country may be less than that of international borders. Morshed, et al (2005) found half of price shock in the case of 25 Indian cities as low as only three months and found strong evidence of relative price convergence for India. Imbs, et al (2005) in their seminal paper showed importance of dynamic aggregation bias in estimating PPP.…”
Section: Literature Reviewmentioning
confidence: 97%